MANAGING UNCERTAINTIES VIA AN EMBEDDED FORESIGHT REGIMEN IN THE NATIONAL POLICY PLANNINGARCHITECTURE - Ariffin, AiniSuzana; Maavak, Mathew; Miles, Ian (International Journal of Engineering Technologies and Management Research, 2018)
National policy planning can be a relatively tortuous process due to rising cross-sectoral complexities and bloated government structures. It is also becoming increasingly difficult to maintain the relevance of national policies in a rapidly-changing global environment. This paper posits that long-term policy relevance can be sustained by embedding a foresight regimen throughout the national policy planning architecture. The proposed foresight template is predicated to enable the monitoring of phases and milestones in the national policy process and thereby be continually adaptable in sync with evolving external developments and internal needs. Malaysia’s automobile industry formed a partial backdrop during the development of this concept paper.